2015
DOI: 10.1590/1983-21252015v28n312rc
|View full text |Cite
|
Sign up to set email alerts
|

CARACTERIZAÇÃO MORFOLÓGICA DE FONTES DE RESISTÊNCIA DE MELOEIRO A Pseudoperonospora cubensis

Abstract: RESUMO: O míldio, causado pelo fungo Pseudoperonospora cubensis é uma das principais doenças foliares que acometem a cultura do meloeiro no período chuvoso da região Nordeste brasileira. O objetivo do presente trabalho foi identificar e caracterizar morfologicamente fontes de resistência de meloeiro a P. cubensis. Trinta e seis acessos e quatro cultivares comerciais foram avaliados em delineamento em blocos casualizados com três repetições. A unidade experimental foi composta por sete plantas. E a avaliação re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
(15 reference statements)
1
7
0
1
Order By: Relevance
“…Thus, it would be possible to identify new botanical varieties suitable for the genetic breeding of the species, since most of the characteristics that indicate the botanical varieties are controlled by a few genes (DOGIMONT, 2011). Indeed, among the melon accessions from family farming, the presence of some sources of resistance to pathogens was identified, such as Rhizoctonia solani 401 (SALES JÚNIOR et al, 2015), Myrothecium roridum (NASCIMENTO et al, 2012), Macrophomina phaseolina 402 (AMBRÓSIO et al, 2015) and Pseudoperonospora cubensis (ALBUQUERQUE et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it would be possible to identify new botanical varieties suitable for the genetic breeding of the species, since most of the characteristics that indicate the botanical varieties are controlled by a few genes (DOGIMONT, 2011). Indeed, among the melon accessions from family farming, the presence of some sources of resistance to pathogens was identified, such as Rhizoctonia solani 401 (SALES JÚNIOR et al, 2015), Myrothecium roridum (NASCIMENTO et al, 2012), Macrophomina phaseolina 402 (AMBRÓSIO et al, 2015) and Pseudoperonospora cubensis (ALBUQUERQUE et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Notwithstanding, Roy et al (2012) found wide variation in wild melons from India and showed that melons of the variety momordica were grown there. Thereafter, with the Great Navigations, it is likely that melons of this variety, grown in several states of the Brazilian semi-arid region, have come from India, as shown in the list of accessions from the collection of the Federal Rural University of the Semi-Arid (ALBUQUERQUE et al, 2015). This assumption gains strength because current reports indicate that melons split when approaching maturity in many areas of Northeast Brazil, a descriptor that is characteristic of the variety momordica.…”
Section: Introductionmentioning
confidence: 99%
“…This precision in selection can be confirmed using genetic parameters, such as heritability and accuracy (Albuquerque et al, 2015). The trait NMLyp in the experiments with controlled infestation had the highest heritability values (74 to 88%), except for trial LAB2 (38%).…”
Section: Resultsmentioning
confidence: 65%
“…High accuracy results in highly reliable genotypic value predictions, and the selection of the best accessions (Albuquerque et al, 2015). Selection accuracy has been used to make inferences in regard to precision, because it is related to the relative coefficient of variation and the number of replications (Resende and Duarte, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…In that season, the high precipitation (> 45m mm) was the main problem for the melon crop. In addition, the occurrence of diseases such as fruit blotches, caused by the bacterium Acidovorax avenae (ALVES et al, 2010), and mildew, caused by the fungus Pseudoperonospora cubensis (ALBUQUERQUE et al, 2015) are frequent. All these factors lead to low productivity and low SS content, thus reducing fruit quality.…”
Section: Resultsmentioning
confidence: 99%